Manajemen Program Bahasa Arab di Pesantren Mahasiswa Firdaus Malang Berdasarkan Teori Henry Fayol - Wiwit Nazilah Utami; Nuril Mufidah; Abdul Malik Karim Amrullah (Universitas Proklamasi 45, 2024)
Management, an important part of human life, will always be needed wherever humans live, including in their work, education, etc. One of the management experts, Henry Fayol, defines management in three terms, i.e.: 1) Management as a process, 2) Management as a collectivity of people who carry out all management activities, and 3) Management as an art and science. Henry Fayol's management theory focuses on how management interacts with its personnel. This research will look at how the Arabic language program is managed at the Firdaus Student Islamic Boarding School Malang based on Henry Fayol's management theory. This research used descriptive qualitative methods with data collection techniques of observation, interviews, and documentation. In implementing its Arabic language program, the Firdaus boarding school has paid proper attention to management functions. Starting from planning, organizing, directing, coordinating, and supervising. The success of this program management can be seen from the success of the Arabic language program at the Firdaus boarding school. The success of the Arabic language program at the Firdaus boarding school can be seen from the alumni who have become experts in Arabic and successful Arabic language teachers in their respective places.